2006
DOI: 10.1590/s1519-69842006000500002
|View full text |Cite
|
Sign up to set email alerts
|

Species composition and structure of Thysanoptera communities in different microhabitats at the Parque Estadual de Itapuã, Viamão, RS

Abstract: Although thrips are known as inhabitants of flowers, they are also abundant and diverse in other microhabitats. There is an information gap concerning them, especially related to the native fauna in southern Brazil. The structure and composition of the thysanopteran community in different microhabitats was studied at the "Parque Estadual de Itapuã" (30° 22' S 51° 02' W), RS, southern Brazil. Between June 1999 and May 2001, branches (n = 1,274), flowers (n = 774), grass tussocks (n = 596) and leaf litter (n = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
0
8
1
1
Order By: Relevance
“…In southern Brazil, other studies in a natural area found a thrips richness in Itapuã State Park (Cavalleri, 2005;Pinent et al, 2005Pinent et al, , 2006 that is double the level observed in our study. However, the incomplete stabilization of the species-accumulation curve indicates that a higher richness of thrips species may be found in the fragments of coastal vegetation sampled.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In southern Brazil, other studies in a natural area found a thrips richness in Itapuã State Park (Cavalleri, 2005;Pinent et al, 2005Pinent et al, , 2006 that is double the level observed in our study. However, the incomplete stabilization of the species-accumulation curve indicates that a higher richness of thrips species may be found in the fragments of coastal vegetation sampled.…”
Section: Discussioncontrasting
confidence: 60%
“…Apart from Treherniella sp., all thrips species sampled in our study have been found in surveys conducted in different states of Brazil, i.e. Piauí and Maranhão (Lima and Zucchi, 2016), Rio Grande do Norte and Rio Grande do Sul (Pinent et al, 2005(Pinent et al, , 2006.…”
Section: Discussionmentioning
confidence: 97%
“…Owing to the unceasing destruction of natural environments, any information on species diversity has become critically important to understand the functioning of natural communities. Thrips are not currently endangered or threatened, and their survival is based on the conservation of their host plants and habitats (Pinent et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…About 520 Thysanoptera species in 139 genera and six families are known from Brazil, representing nearly 10% of the worldwide described species (Monteiro 2002). However, recent studies and observations indicate a large number of unrecorded and undescribed species in Brazilian territory (Pinent et al 2006, Cavalleri & Kaminski 2007.…”
mentioning
confidence: 99%